2010
DOI: 10.1177/1082013209353236
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of a Spray-Dried Soymilk Powder and Changes Observed During Storage

Abstract: Physical characterization of a soymilk powder was carried out by electron microscopy. Chemical characterization was analyzed by proximate analysis, mineral composition by atomic absorption spectrometry, fatty acid composition by gas chromatography and protein composition by electrophoresis. The powder consists of large granules of 60-80 μm, which may be hollow, with smaller granules of 10-20 μm attached to them. Powder particles are covered by a layer of fat. During storage at 25 °C fat is spreading over the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
26
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(33 citation statements)
references
References 29 publications
6
26
0
1
Order By: Relevance
“…Ash, fat, and protein content were statistically higher in raw almond than in milk or powder, which is consistent with the addition of maltodextrin. All three components (ash, fat, and protein) were recuperated in the powder; a similar tendency was also observed for spray‐dried soymilk powder . Carbohydrates were significantly higher in almond milk powder (366 g kg −1 mean value) than in the raw material (202 g kg −1 ), due to the maltodextrin added to protect the bacteria and to enhance the spray‐drying process.…”
Section: Resultssupporting
confidence: 65%
See 2 more Smart Citations
“…Ash, fat, and protein content were statistically higher in raw almond than in milk or powder, which is consistent with the addition of maltodextrin. All three components (ash, fat, and protein) were recuperated in the powder; a similar tendency was also observed for spray‐dried soymilk powder . Carbohydrates were significantly higher in almond milk powder (366 g kg −1 mean value) than in the raw material (202 g kg −1 ), due to the maltodextrin added to protect the bacteria and to enhance the spray‐drying process.…”
Section: Resultssupporting
confidence: 65%
“…Approximately 2 g of powder was dried in a hot‐air oven at 103 ± 2 °C and the weight was controlled daily until a constant weight was reached …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, storage resulted in an increase in the free fatty acid content in all samples of groundnut milk powder (Table 1, Figure 5) which may be due to the breaking of long chain fatty acid into individual fatty acid entities (Siwach et al, 2016). Similarly, Osthoff, Hugo, Wyk, Wit, and Meyer (2010) reported deterioration in lipid quality of soymilk powder when stored at temperature greater than 25 C. The percent free fatty acid values in groundnut milk powder were 0.481% as oleic acid in fresh samples, upon storage these values recorded an increase (0.550-2.021% and 0.531-1.870% in aluminum foil package and metal tin can, respectively). It was observed that the free fatty acid (FFA) increase was relatively higher in aluminum foil package than metal tin can.…”
Section: Free Fatty Acid Of Groundnut Milk Powdermentioning
confidence: 99%
“…Regarding soy foods, Bhardwaj, Hamama, Rangappa, Joshi, and Sapra (2007) stated that their mineral content is affected by soybean genotype and growing location. However, soymilk powder, soy-yogurt and tofu are characterized by a high Ca and Mg content and low concentration of Fe, Zn, Cu and Mn (Adentunji, Betiku, & Solomon, 2006;Bhardwaj et al, 2007;Osthoff, Hugo, Van Wyk, De Wit, & Meyer, 2010).…”
Section: Fatty Acid Compoundsmentioning
confidence: 99%